The Creativity of Social Dreaming. - Lawrence, Gordon (Karnac Books, 2010)
This broad range of papers covers different aspects of social dreaming. The book begins with a summary of the Social Dreaming Matrix conceptualised as a temporary system with its intakes, transformation processes and outputs. The remaining chapters cover social dreaming in different contexts including, amongst others, from the perspectives of art, architecture, theatre, working with immigrants, with pilots and lawyers and family mediators and hospitals. All the papers cover areas outside of the goal orientated activities of the institution, and examine what they may be saying about the organizat.